Anticancer effects of flavonoids on melanoma cells: are murine cells more sensitive compared to humans? - Katrin Sak (International Journal of Phytomedicine, 2013)
In the past few decades, research in new drugs for treatment of oncological disorders has refocused on naturally occurring products. Among various plant-derived compounds flavonoids are considered as promising chemopreventive and chemotherapeutic agents exerting specific antiproliferative and cytotoxic activities towards various cancer cell lines. Such tumoricidal action can depend on the structure of flavonoids and their concentrations, but also on the cellular milieu and cancer type. Analysing the anticancer effects of various flavonoids on different human and murine melanoma cell lines, one further aspect influencing the antineoplastic action of flavonoids is pointed out in this article, i.e. the species origin of malignant cells. It is shown that murine melanoma cells tend to exert somewhat lower resistance to different flavonoids compared to human melanoma cells, emphasising that anticancer effects exhibited by natural polyphenolic agents in mouse cells can not be directly extrapolated to humans.